Children's contact with people with disabilities and their attitudes towards disability: a cross-sectional study. Issue 9 (23rd April 2016) - Armstrong, Megan; Morris, Christopher; Abraham, Charles; Ukoumunne, Obioha C.; Tarrant, Mark
Abstract: Purpose : To explore the association between children's self-reported contact with people with disabilities and attitudes towards them, as well the potential mediating influence of anxiety about interacting with people with disabilities and empathy for them. Method : 1881 children, aged 7–16 years, from 20 schools in South West England completed a survey assessing their contact with people with disabilities and their attitudes towards them. Anxiety about interacting with people with disabilities and empathy towards them were examined as potential mediators. Gender, school year, perceived similarity between people with and without disabilities, proportion of children with additional needs at the school and socioeconomic status (SES) were assessed as moderators. A random effects ("multilevel") regression model was used to test the contact–attitude association and moderation, and path analysis was used to test for mediation. Results : Participants with more self-reported contact reported more positive attitudes towards disability ( p  < 0.001). Less anticipated anxiety and greater empathy together mediated around a third of this association. Only school year moderated the contact–attitude association (affective attitudes), with stronger contact–attitude associations in primary school children than secondary school children. Conclusions : Self-reported contact was observed to be associated with more positive attitudes towards disability, which was partially mediated by empathy and anxiety. Providing opportunities for contact with people with disabilities that reduces anxiety and increases empathy may improve attitudes to disability and merits evaluation in interventions. Implications for Rehabilitation: Children who reported greater levels of contact with people with disabilities had more positive attitudes towards disability. Anxiety about interacting with people with disabilities and empathy towards them partially mediated the contact–attitude associations. Providing opportunities for contact with people with disabilities, reducing anxiety and increasing empathy may improve children's attitudes to disability.